2004
DOI: 10.1074/jbc.m402898200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology of the DrrB Protein of the Doxorubicin Transporter of Streptomyces peucetius

Abstract: Daunorubicin and doxorubicin, two commonly used anticancer agents, are produced by the soil bacterium Streptomyces peucetius. Self-resistance to these antibiotics in S. peucetius is conferred by the drrAB locus that codes for two proteins, DrrA and DrrB. DrrA is an ATPbinding protein. It belongs to the ABC family of transporters and shares sequence and functional similarities with P-glycoprotein of cancer cells. DrrB is an integral membrane protein that might function as a transporter for the efflux of daunoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
0
33
0
1
Order By: Relevance
“…DrrA consists of an ABC-type NBD, while DrrB is an IM protein. Using gene fusions, a topology model has been proposed for DrrB, consisting of eight membrane-spanning segments with both N and C termini in the cytoplasm (164). Cysteine cross-linking revealed a motif within the N-terminal tail of DrrB that may be a modified version of the EAA motif present in ABC importers (236,392).…”
Section: Class 3 Abc Systems That Are Probably Not Importersmentioning
confidence: 99%
“…DrrA consists of an ABC-type NBD, while DrrB is an IM protein. Using gene fusions, a topology model has been proposed for DrrB, consisting of eight membrane-spanning segments with both N and C termini in the cytoplasm (164). Cysteine cross-linking revealed a motif within the N-terminal tail of DrrB that may be a modified version of the EAA motif present in ABC importers (236,392).…”
Section: Class 3 Abc Systems That Are Probably Not Importersmentioning
confidence: 99%
“…In addition, RHA1 likely produces several bioactive compounds of its own (see below). Indeed, DrrA (ro06841) and DrrB (ro06840) homologs share 65% and 51% amino acid sequence identity with the daunorubicin transporters from Streptomyces peucetius (16). Although many MFS transporters in RHA1 are homologs of tetracycline transporters (e.g., ro04399), RHA1 is not resistant to tetracycline, suggesting that these proteins transport other compounds.…”
mentioning
confidence: 99%
“…However, in the absence of functional FtsH, the DrrB protein accumulates even in the absence of DrrA confirming that FtsH monitors the folding status of DrrB and removes it if it is improperly assembled. The molecular details of proteolysis of DrrB by FtsH are currently unknown, however, based on the prevalent model for its action (8,26) we assume that FtsH could initiate proteolysis of DrrB either at the N-or the C-terminal end (both of which are found in the cytoplasm (27)). Crosslinking studies previously showed that the N terminus of DrrB is the major site of interaction with DrrA (3,27); therefore we propose that proteolysis of DrrB initiates at its N-terminal tail, and binding of DrrA to this region of DrrB protects it from proteolysis by FtsH.…”
Section: Discussionmentioning
confidence: 99%